Implementasi Metode Talqin Dalam Pembelajaran Tahfizhul Qur’an Di Sekolah Dasar Al Hanief Kota Bekasi - Salafudin Salafudin; Darwis Darwis (Turabian: Jurnal Pendidikan Islam, 2023)
This study contains an analysis of the preparation for the implementation of talqin in learning tahfizhul Qur'an at AL HANIEF Elementary School; the form of implementation of the talqin method in learning tahfizhul Qur'an; and analysis of the factors supporting and inhibiting the implementation of talqin. The approach used is qualitative with descriptive analysis method. Data collection techniques were carried out by: interviews, observation and documentation. The data analysis process is carried out through collecting, sorting, and checking the validity of the data. The results of this study indicate that: At Sekolah Dasar AL HANIEF Rawalumbu, Bekasi City has implemented the tahfizhul Qur'an program by implementing the talqin method in the learning process. The process starts from planning, then implementing talqin with certain shapes and patterns so that a verse can be memorized. As a result, 90% of AL HANIEF Elementary School students can reach the target of memorizing Juz 30 when they graduate from this school, even if only by allocating 2 hours of lessons (30 minutes X 2), or just 1 hour a week. There are factors that support and hinder the implementation of this talqin. Supporting factors: School readiness in carrying out the tahfizhul Qur'an program; the role and competence of the tahfizh teacher; enthusiastic students; the activeness and creativity of the tahfizh teacher; conducive school environment; parental support; and control and evaluation. While the inhibiting factors: loosening student enthusiasm; Diversity of student backgrounds; limited control and supervision of students outside of school; and the lack of time to learn tahfizhul Qur'an in schools and the limited availability of tahfizh teachers with this talqin method. The results of this study indicate that the talqin method is an effective approach in learning tahfizhul Qur'an in schools, as has been implemented in Sekolah Dasar AL HANIEF. If this method is implemented better, the results will be even better